Multifunctional nanocellulose hybrid films: From packaging to photovoltaics - Valdez Garcia, Joaquin; Boding, Anna; Yang, Xuan; Nizamov, Rustem; Reid, Michael S.; Junel, Kristina; Miettunen, Kati; Abitbol, Tiffany; Kaschuk, Joice (Elsevier BV, 2025)
This study aimed to develop eco-friendly multifunctional nanocellulose (NC) hybrid films with tailored properties for versatile applications including packaging and photovoltaics. Hybrid films composed by cellulose nanocrystals (CNC) and carboxymethylated cellulose nanofibrils (CNF) were produced at various mass ratio (CNC - 100:0 to 0:100). Montmorillonite clay (MTM) was incorporated (50 % by mass) into the CNC:CNF films. CNC-only films easily dispersed in water, but by adding CNF or MTM, the structural integrity was enhanced. Films with ≥50 % CNF and MTM had a strength reduction of 9–35 % and increased brittleness. The hybrid films presented transmittance above 60 % and haze varying from 5 % to 60 % at 550 nm which can be a beneficial for light management. All films kept color stability over 1000 h of artificial sunlight, a critical packaging feature for long-term storage. CNC: CNF films without MTM showed better potential for optoelectronic applications due to higher transmittance and smoother surfaces, while those with MTM presented UV protection (up to 250 nm) and swelling resistance (28–53 %) which could also benefit optoelectronics increasing their lifespan. Balancing the hybrid films composition is key for optoelectronics, while packaging applications tolerate broader compositions. These findings demonstrate the versatility of NC hybrid films in creating sustainable materials for diverse applications.